2020
DOI: 10.35333/jrp.2020.194
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitory potencies of new pyrazoline derivatives

Abstract: Alzheimer's disease (AD) has no current cure and its mechanism is not fully known, but treatments for symptoms are available. Acetylcholinesterase (AChE) has been reported to be an applicable therapeutic target in patient with AD. Acetylcholinesterase inhibitors (AChEIs) are commonly used for it. For this purpose, novel series of pyrazoline based compounds [2-(3-(4-methoxyphenyl)-5-aryl-4,5-dihydro-1H-pyrazol-1-yl)benzo[d]thiazole, 1-9] were synthesized and AChE inhibitory potencies were reported here. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Although the pathophysiology of AD has not been clearly established, the cholinergic hypothesis is one of the most accepted causes. According to the cholinergic hypothesis, AD is associated with alterations of cholinergic markers such as cholinesterases (Tuğrak, Gül & Gülçin, 2020;Kahraman et al, 2019). IC 50 values of the extracts were above 200 µg/mL on AChE for all extracts, while IC 50 values for BuChE were determined as below 100 µg/ mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathophysiology of AD has not been clearly established, the cholinergic hypothesis is one of the most accepted causes. According to the cholinergic hypothesis, AD is associated with alterations of cholinergic markers such as cholinesterases (Tuğrak, Gül & Gülçin, 2020;Kahraman et al, 2019). IC 50 values of the extracts were above 200 µg/mL on AChE for all extracts, while IC 50 values for BuChE were determined as below 100 µg/ mL.…”
Section: Discussionmentioning
confidence: 99%
“…CEP-3 showed more significant tyrosinase inhibitory effects than kojic acid as a positive control (p<0.001) in this study. Studies in the literature show that antioxidant compounds have tyrosinase inhibitory properties (Wang et al, 2018;Morais et al, 2018;Sun, Guo, Zhang & Zhuang, 2017). In this study, we determined that extracts with a high antioxidant effect showed high tyrosinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Currently, some cholinesterase inhibitors (ChEIs) including tacrine, rivastigmine, donepezil, and galantamine are approved for the treatment of AD. [20] It is known that most of these putative ChEIs used today have some side effects including gastrointestinal anomalies, nausea, diarrhea, and hepatotoxicity. It was reported that tacrine, one of these standard clinical inhibitors, had some side effects including nausea, vomiting, stomach upset, weight loss, agitation, diarrhea, shaking, and skin rash.…”
Section: Introductionmentioning
confidence: 99%
“…So, AChE inhibition has been the most successful and common approach for treatment of AD to date [19] . Currently, some cholinesterase inhibitors (ChEIs) including tacrine, rivastigmine, donepezil, and galantamine are approved for the treatment of AD [20] . It is known that most of these putative ChEIs used today have some side effects including gastrointestinal anomalies, nausea, diarrhea, and hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45] Currently, some cholinesterase inhibitors including tacrine, rivastigmine, donepezil, and galantamine are approved for the treatment of AD. [46] Both AChE and BChE are the two brain enzymes targeted by these drugs. It is known that most of these putative cholinesterase inhibitors used today have side effects including gastrointestinal anomalies such as nausea, diarrhea, and hepatotoxicity.…”
mentioning
confidence: 99%